Cytotoxicity study of Schizophyllum commune extract towards DF-1 cell line - Abd rahman, Nur Rahilah; Ahmad Raus, Raha; Mel, Maizirwan (2012)
Schizophyllum commune is a filamentous fungus widely known and distributed across the world continents. Although S. commune was acknowledged for its medicinal properties in countries like China and Japan, the Malaysian strain of S. Commune has not been fully utilized and developed. These basidiomycetes can be found abundantly in rubber plantations across Malaysia especially after raining season. S. commune excreted an exopolysaccharide known as Schizophyllan which can be identified as a homoGlucan containing a β-(1,3)-linked backbone with single β-(1,6)-linked glucose side chains at every third residue. Schizophyllan is believed to have an antiviral, antimicrobial as well as anticancer activity. The purpose of this study is to observe the cytotoxicity effect of S. commune extract towards the DF-1 cell line. The selected Malaysian strain of S.commune mycelia were cultivated by liquid fermentation using shake flasks in selective media and under certain condition to produce the secondary bioactive compound. Compound was extracted by addition of isopropanol that will be separated later using centrifugation. The analysis of S. commune extract by FTIR showed the weak bond at 890 cm-1 as evidenced of the β-glycosidic linkage characteristic. The cytotoxicity analysis showed only 37 percent of inhibition rate of DF-1 cell line viability for 1 mg/ml of S. commune extract and the value of IC50 is higher 100 mg/ml showed there was no cytotoxic effect. Therefore, the S. commune is safe to be used for further study involving this cell line.